Effect of Polyethylene Glycol and Humic Acid Coating on NPK Release From Controlled-Release Fertilizer - null Suwardi; Dyah Tjahyandari Suryaningtyas; Abdul Ghofar; Mochamad Rosjidi; Anwar Mustafa; Hens Saputra (The Scientific World Journal)
Plants require essential macronutrients such as nitrogen (N), phosphorus (P), and potassium (K), but their availability in soil is often inefficient due to evaporation, leaching, and binding. Controlled-release fertilizers (CRFs) provide a solution by regulating nutrient release over time. This study evaluates the effects of two coating materials, polyethylene glycol (PEG) and humic acid, on the release patterns of N, P, and K during an 18-week incubation using Inceptisol from Bogor, Indonesia. Various CRF treatments were tested, including uncoated (A1, A2), PEG-coated (B1, B2), and humic acid–coated (C1, C2) formulations. Results showed that CRF with PEG (B2) demonstrated slower N release, with ammonium levels decreasing from 32.22% in week 1 to 9.36% by week 18. Nitrate release increased steadily from 26.37% to 37.36% between weeks 3 and 18. In contrast, CRF with humic acid (C2) showed slower nitrate release, reaching 36.26% by the end of incubation. P release patterns were similar across treatments, while K release was lowest in the humic acid–coated treatment (C2) at 24.48%. These findings underline the potential of coating materials like PEG and humic acid to optimize nutrient release, enhancing agricultural efficiency.